#TITLE_ALTERNATIVE# - WITA UTAMI (NIM: 20514020), HANIFAH
Chalcone and their derivatives (2',4'-dihydroxy-5',6'-dimethoxychalcone, and 2',4'-dihydroxy-3',5',6'-trimethoxychalcone) are secondary metabolite compounds that have a biological activity, particularly as a drug of antitumor, antimalaria and anticancer. Chalcone and their derivatives were also becoming important intermediate compounds in organic synthesis. Chalcone and their derivatives can be synthesized by aldol condensation reaction. The condensation reaction is a coupling reaction of two molecules or more than which is producing a larger molecule and a small molecule (such as water). The aldol condensation is a reaction between aldehyde molecule which has a hydrogen α with the others. The aldehyde in alkaline solution (NaOH) generated an enolate ion and then it was interacted with the carbonyl group of another aldehyde molecule. The synthesis of chalcone and their derivatives by aldol condensation reaction consist of four steps, the first is formation of enolate ion, nucleophilic addition reaction, proton transfer (protonation), and dehydration reaction. Mechanism reaction of aldol condensation contain the fundamental aspects of the structure information, thermodynamic, and kinetic aspects. The purpose of this research studied the mechanism reaction in the synthesis of chalcone by aldol condensation reaction, was seen from the aspect of the structure, thermodynamic, and kinetic through computational study with ab initio computational. Ab initio computational study is using DFT (Density Functional Theory) as theoretical approach, the functional of B3LYP, with 6-31G(d) as basis set. The calculation result obtained ΔGo of chalcone and their derivatives (2',4'-dihydroxy-5',6'-dimethoxychalcone and 2',4'- dihydroxy-3',5',6'-trimethoxychalcone) are 17.5678, 2.4994 and 13.0892 kcal/mol respectively. So 2',4'-dihydroxy-5',6' dimethoxychalcone compound is more stable than chalcone and 2',4'-dihydroxy-3',5',6'-trimethoxychalcone compounds. The calculation result obtained ΔHo of chalcone and their derivatives (2',4'-dihydroxy- 5',6' dimethoxychalcone and 2',4'-dihydroxy-3',5',6'-trimethoxychalcone) are 16.2512, 0.2874 and 12.7485 kcal/mol respectively, so synthesis of chalcone and their derivatives by aldol condensation reaction is a endothermic reaction. 2',4'- dihydroxy-5',6'-dimethoxychalcone compound is more easy to produce the product by aldol condensation reaction than chalcone and 2',4'-dihydroxy-3',5',6'- trimethoxychalcone compounds. The activation energy (Ea) for TS1, TS2, TS3 and TS4 chalcone are 17.4529, 50.8301, 100.0758, 56.1470 kcal/mol respectively. Nucleophilic addition reaction and dehydration reaction have the same activation energy, because process of collision molecule reactan in two step reaction have the same process. The rate of reaction for formation of enolate ion, nucleophilic addition reaction, proton transfer (protonation), and dehydration reactions are 11.7137 ˣ 10-13, 7.2962 ˣ 103, 1.02325 ˣ 10-32 and 3.5412 ˣ 10-29 s-1 respectively. So nucleophilic addition reaction step is more easy to react than the other steps, while proton transfer (protonation) step is determinant of the rate of all reaction in synthesis chalcone by aldol ccondensation reaction.